Comparison of different drug regimens for the treatment of loiasis—A TropNet retrospective study - Gobbi, Federico; Bottieau, Emmanuel; Bouchaud, Olivier; Buonfrate, Dora; Salvador, Fernando; Rojo-Marcos, Gerardo; Rodari, Paola; Clerinx, Jan; Treviño, Begoña; Herrera-Ávila, Juan Paulo; Neumayr, Andreas; Calleri, Guido; et al. (PLOS Neglected Tropical Diseases, 2018)
Author summary Loa loa is a worm which infects millions of people living in wide forested areas of central Africa. The infection is rarely diagnosed outside Africa, and cases are mainly referred to referral centers on tropical medicine. Aim of this study was to describe the treatment and management of patients diagnosed with loiasis in some referral centers for tropical medicine in Europe. The results showed that different health centers treat the patients with different drugs/drug combinations. On the basis of the availability of the drugs and on the data observed, common protocols might be recommended for the participating centers.